The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/prs.0000000000009536
|View full text |Cite
|
Sign up to set email alerts
|

Breast Resection Weight Prediction and Insurance Reimbursement in Reduction Mammaplasty: Which Scale Is Reliable?

Abstract: Background: Many insurance companies in the United States rely on the Schnur sliding scale to predict resection weights to determine medical necessity for breast reduction surgery. Accurate methods to predict resection weights are needed to avoid insurance denials. The authors compared the accuracy of formulas such as the Schnur, Appel, Descamps, and Galveston scales in predicting resection weights, and assessed whether they influence insurance coverage decision. Methods: A retrospective review of bilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…1 Within this context, plastic and reconstructive surgery represents a sizeable portion of the unmet surgical need in LMICs, accounting for approximately 16% of all surgically treatable conditions. 2 To address this challenge, a comprehensive and multifaceted approach is required.…”
Section: A Modified Template For Microtia Reconstruction Tested By Su...mentioning
confidence: 99%
See 3 more Smart Citations
“…1 Within this context, plastic and reconstructive surgery represents a sizeable portion of the unmet surgical need in LMICs, accounting for approximately 16% of all surgically treatable conditions. 2 To address this challenge, a comprehensive and multifaceted approach is required.…”
Section: A Modified Template For Microtia Reconstruction Tested By Su...mentioning
confidence: 99%
“…5 Insurers prefer quantitative criteria and therefore continue using the Schnur scale despite mounting evidence denouncing its relevance, as well as the existence of more reliable resection weight calculations. 2,6 Numerous studies have demonstrated that resection weights smaller than Schnur's 22nd percentile or the arbitrary 500-g weight minimum set by some insurers substantially relieve macromastia-related symptoms. 8 There is no significant difference in symptom relief across all resection weights and body mass index values.…”
Section: Viewpointsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the United States, insurance providers employ assessment tools, such as the Schnur scale, to determine the minimum breast resection weights that justify the medical need for reduction surgery. Typically, insurance companies will cover this procedure if the amount of tissue to be removed exceeds the 78th percentile based on the individual's body surface area or weighs more than 500 g [4].…”
mentioning
confidence: 99%